DISCOURSE ANALYSIS ON TAYLOR SWIFT’S YOU NEED TO CALM DOWN MUSIC VIDEO WITH SEMIOTIC APPROACH - Jonathan Irene Sartika Dewi Max; Aries Utomo (Sanata Dharma University, 2021)
As a mode of expression, music video involves the process of meaning-making. Its unique method of assembling symbolic codes should be apprehended differently from films even though some film technical terms are found applicable. This research takes Taylor Swift’s music video for her song You Need to Calm Down (YNTCD) which won two MTV VMA as Video of the Year and Video for Good in 2019. Barthes’s theory of semiotics is firstly applied to scrutinize the music video which is done by answering how the denotation and connotation meaning is made to respond to these issues. Discourse analysis is then applied to study what discourses are influential in the signification system of the music video. As a response to issues of hate speech, LGBTQ, and media toxic contestation, meaning in this video is built by (1) the objects symbolizing personal experiences, (2) borrowing meaning from the iconic show, (3) cameos demonstrating social conflict, (4) stage-setting exemplifying media toxic contestation, and (5) the painting indicating historical context. Thus, the YNTCD music video symbolically voices a counter-discourse to the mentioned social problems.